Awareness of oral cancer and precancer among final year dental undergraduates in Ukraine - Kolenko, Yulia (Journal of Education, Health and Sport, 2016)
Kolenko Yulia. Awareness of oral cancer and precancer among final year dental undergraduates in Ukraine. Journal of Education, Health and Sport. 2016;6(3):106-112. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47867 http://ojs.ukw.edu.pl/index.php/johs/article/view/3426 https://pbn.nauka.gov.pl/works/721251 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. AWARENESS OF ORAL CANCER AND PRECANCER AMONG FINAL YEAR DENTAL UNDERGRADUATES IN UKRAINE Kolenko Yulia1 1Bogomolets National medical university, Kyiv, Ukraine Correspondence: Kolenko Yulia, associate professor of Operative Dentistry department, Bogomolets National medical university, Zoollogichna street, 1, Kyiv, Ukraine. Tel: +380 50 772 7375. E-mail: kolenko.julia@gmail.com Abstract Background: Oral cancer presents with high mortality rates, and the likelihood of survival is remarkably superior when detected early. Health care providers, particularly dentists, play a critical role in early detection of oral cancers and should be knowledgeable and skillful in oral cancer diagnosis. Purpose: The objective of the present study was to assess the comprehensive awareness of final year dental undergraduates of Medical Universities and Institutes Ukraine concerning oral cancer and oral potentially malignant disorders. Materials and Methods: A pretested self-administered questionnaire was distributed to fifth year dental students. Questions relating to knowledge of oral cancer, risk factors, and opinions on oral cancer prevention and practices were posed. Results: Only a small proportion of both groups of students expressed confidence in their knowledge and skills in oral cancer prevention and detection. This study revealed areas of deficiency in the awareness of these students concerning oral cancer and OPMD. It points to a necessity to strengthen these aspects of medical and dental undergraduate curricula. Conclusions : The findings of the present study suggest that here is a need to reinforce the undergraduate dental curriculum with regards to oral cancer education, particularly in its prevention and early detection. Keywords: dental students, knowledge, opinions, dental education, oral cancer, oral potentially malignant disorders, curriculum.